Anxiety and distress following receipt of results from routine HPV primary testing in cervical screening: The psychological impact of primary screening (PIPS) study. Issue 8 (23rd July 2019) - McBride, Emily; Marlow, Laura A.V.; Forster, Alice S.; Ridout, Deborah; Kitchener, Henry; Patnick, Julietta; Waller, Jo
Abstract : We used a cross‐sectional survey to examine short‐term anxiety and distress in women receiving different results following routine human papillomavirus (HPV) primary testing at cervical screening. Participants were women aged 24–65 ( n = 1, 127) who had attended screening at one of five sites piloting HPV primary screening in England, including a control group with normal cytology who were not tested for HPV. Women completed a postal questionnaire ~2 weeks after receiving their screening result. Unadjusted mean anxiety scores ranged from 32.9 (standard deviation [SD] = 12.2) in HPV‐negative women to 42.1 (SD = 14.9) in women who were HPV‐positive with abnormal cytology. In adjusted analyses, anxiety was significantly higher in women testing HPV‐positive with either normal cytology (mean difference [MD] = 3.5, CI: 0.6–6.4) or abnormal cytology (MD = 7.2, CI: 3.7–10.6), than the control group. Distress was slightly higher in women who tested HPV‐positive with abnormal cytology (MD = 0.9, CI: 0.02–1.8), than the control group. We also found increased odds of very high anxiety in women who tested HPV‐positive with normal or abnormal cytology compared to the control group. This pattern of results was only observed among women receiving their first HPV‐positive result, not among women found to have persistent HPV at 12‐month follow‐up. Testing HPV‐positive with normal cytology for the first time, is associated with elevated anxiety despite carrying very low immediate cervical cancer risk. However, receiving the same test result at 12‐month early recall does not appear to be associated with higher anxiety, suggesting anxiety may normalise with repeated exposure and/or over time. Abstract : What's new? While a positive test for human papillomavirus (HPV) with negative cytology is associated with low cervical cancer risk, recall for additional HPV testing may have undesirable psychological impacts. In this study, involving women who participated in HPV primary screening in England, women who were informed of an HPV‐positive result for the first time experience increased anxiety and concern. Meanwhile, positive HPV testing at 12‐month recall had little adverse psychological impact, suggesting that anxiety concerning a positive HPV result is relatively short‐lived. Nonetheless, strategies should be in place to mitigate anxiety in women receiving a positive result for the first time.